Legal Policy and Model of Criminal Responsibility in the Crime of Smuggling by Corporations in Indonesia - Afan Beny Arseno (JUSTICES: Journal of Law, 2024)
The aim of this research is to determine criminal law policies and models of criminal responsibility for criminal acts of smuggling of goods by corporations in Indonesian criminal legislation. This research is normative legal research, namely research conducted using data in the form of theories, concepts and regulations regarding legal issues regarding criminal law policies to deal with the problem of criminal acts of smuggling goods committed by corporations. The results of the research conclude that criminal liability in criminal acts of smuggling by corporations in Indonesia refers to a legal scheme where corporations are the subject of criminal law and are regulated in Law no. 17 of 2006 concerning Amendments to Law no. 10 of 1995 concerning Customs. The additional models of responsibility that can be applied in smuggling cases include: first, the responsibility of corporate managers as perpetrators and administrators who are subject to criminal responsibility (identification theory) which is based on article 59 of the Criminal Code. Second, the model of corporate responsibility as perpetrators and administrators who are responsible (vicarious liability) is based on articles 82 and 85 paragraph 2 of the Limited Liability Company Law. Third, the model of corporate responsibility as perpetrator and also as responsible (stricht liability) which is based on the logical consequences of applying corporations as subjects of criminal law.